Composite Films Based on Styrene-co-butyl-acrylate with Colemanite and Calcium Bentonite Mineral Fillers - Guven, O.; Karakas, F.; Kaya, M. A.; Yildirim, H.; Celik, M. S. (SPRINGER, 2014)
Composites are engineered materials made from two or more constituent materials, which remain separate and distinct on the macroscopic level within the finished structure and also with significantly different physical or chemical properties. In recent years, there has been a great interest in polymer/inorganic composites, which stems from their improved properties. Mineral fillers in composites are widely used in industrial applications such as adhesives and paints. They provide better mechanical properties and thermal resistance to the systems and also reduce manufacturing costs. In this study, a comparative evaluation of colemanite and calcium bentonite minerals used as a filler in an aqueous polymer emulsion (styrene-co-butyl acrylate copolymer) is performed. The effect of amount and type of mineral additives on the mechanical properties of composites is investigated. Meanwhile, a comparison between colemanite and calcium bentonite is made on the basis of their different dispersion characteristics in a polymeric matrix. The degree of interfacial interaction between the filler and polymeric matrix is also modeled using the B parameter.
Keywords: styrene-co-butyl acrylate copolymer; colemanite; calcium bentonite; composite; mechanical properties; MECHANICAL-PROPERTIES; SILICATE NANOCOMPOSITES; PARTICLE-SIZE; CLAY; CACO3; Mechanics; Materials Science; Polymer Science